Post Covid Care Through Ayurveda - Rastogi, Gaurav Kr; Dwivedi, Anjana; Bilas, Rajeev Narayan (International Research Journal of Ayurveda & Yoga, 2022)
The pathogen responsible for the COVID 19 pandemic is the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). This has resulted in a worldwide health care crisis and strained health resources. As if becoming infected with COVID 19 wasn’t terrible enough, many people have found the journey to recovery to be arduous and demanding. The degree and extent of viral assaults in different cell types and organs determine what happens following the acute phase of SARS-CoV-2 infection. Patients who have recovered from an acute COVID 19 infection may continue to have a range of signs and symptoms, such as weariness, body aches, cough, sore throat, trouble breathing, and so on. As a result, all post-COVID recovering patients require a holistic approach to follow-up treatment and well-being. Different Ayurvedic therapy procedures (including Ahara-Vihara and Aushdhi) can be used to treat post-COVID sequelae and have been shown to be quite effective in helping patients recover.